A New Time-Use Diary App to Measure Parental Investments - Maria Bigoni; Stefania Bortolotti; Margherita Fort; Annalisa Guarini; Daniela Iorio; Chiara Monfardini; Alessandra Sansavini; Davide Sansone; Chiara Suttora (Institute of Labor Economics (IZA), 2023)
We introduce a new app that collects 24-hour parental time diaries. To assess its validity, we leverage data from a sample of more than 500 parents with pre-school aged children. Our findings show that our tool is reliable and delivers high-quality data. By exploiting contextual information on the child's involvement and feelings during each activity performed with the parent, we construct new measures of parental investments that capture the quality of daily parent-child interactions. We analyse how these novel measures relate to alternative definitions and discuss the potential advantages of the adoption of our approach to time-use measurement in the rapidly growing field of research on the role of parental investments in child development.
Keywords: C81; J13; J24; 330; human capital formation; parents; time inputs; app-based survey